Perinatal Outcome of Oligohydramnios in tertiary level hospital (Journal of Dhaka National Medical College & Hospital, 2025)
Background: Oligohydramnios is being an upcoming challenge both for obstetrician and for pediatricians. Its incidence is 2.3% of all the pregnancies. It is often associated with post term pregnancy, premature rupture of membrane (PROM), intra uterine growth retardation (IUGR),congenital malformation, renal agenesis, obstructed uropathy etc. So, it is very important to assess amniotic fluid index (AFI) to find out the high-risk group of oligohydramnios.Objective: To assess the effect of oligohydramnios on perinatal outcome.Methods: This cross-sectional observational study was conducted at the Department of Obstetrics and Gynaecology of Dhaka National Medical College Hospital from April to September in 2019.Fifty-eight women admitted with isolated Oligohydramnions at term irrespective of their parity were included for the study subjects. The computer-aided statistical software SPSS version 22 was used to analyze the data that was collected through a pre-formed questionnaire. Tables and graphs were used to present the data.Result: This study showed that among study group 42(72.4%) had borderline oligohydramnios and 16(27.6%) had severe oligohydramnios. In severe oligohydramnios group caesarean section was significantly higher than borderline oligohydramnios group. 20.7% were normal vaginal delivery, 3.4% were assisted vaginal delivery and 75.9% were caesarean section. Among 58 patients 29.3% were post term deliveries (41 to 42 completed weeks); 70.7% patients were delivered by 37 to 40 completed weeks. 39.7% babies had suffered from neonatal complications. Among them 22.4% suffered from birth asphyxia, 12.1% from meconium aspiration syndrome. Early neonatal death was 3.4% and still birth was 1.7% mainly due to severe birth asphyxia. Alive take home newborn were 94.8%. Among 55 alive babies, 41.8% babies were admitted in neonatal ICU.Conclusion: Oligohydramnios was responsible for a significantly higher rate of LUCS due to fetal distress at term. Neonatal morbidity like admission in neonatal ward was 41.8% in women with oligohydramnios. Oligohydramnios was increasingly linked to perinatal and neonatal complications. Consequently, each case of oligohydramnios requires meticulous assessment, and appropriate preventive and therapeutic interventions should be implemented accordingly.J.Dhaka National Med. Coll. Hos. 2025; 31 (01): 14-20